2004
DOI: 10.1038/sj.ijir.3901267
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunctions in HCV patients and its correlations with psychological and biological variables

Abstract: The frequency of sexual dysfunction (SD) is not very well known in patients with chronic hepatitis C. In this study, the prevalence of SD and its correlations with psychological and biological variables was assessed in 46 HCV positive patients. The mean age of patients was 46.4+/-9.4 y; the mean duration of HCV infection was 43.4+/-34.0 months; 52% were male; 89% were living with a spouse. SD was assessed using the Arizona Sexual Experiences Scale (ASEX), the level of anxiety and depression measured with the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 14 publications
3
36
1
Order By: Relevance
“…22 Soykan et al reported that sexual dysfunction was in (21%) of the cases with chronic HCV. 15 Further more Danoff et al and Foster reported in accordance with our results strong association between sexual dysfunction and advanced hepatic fibrosis or cirrhosis. 23,24 HBV positive patients 11.8% reported sexual dysfunction, remaining had HBV+HCV positive 2.9%, HBV+HDV positive 1.5%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…22 Soykan et al reported that sexual dysfunction was in (21%) of the cases with chronic HCV. 15 Further more Danoff et al and Foster reported in accordance with our results strong association between sexual dysfunction and advanced hepatic fibrosis or cirrhosis. 23,24 HBV positive patients 11.8% reported sexual dysfunction, remaining had HBV+HCV positive 2.9%, HBV+HDV positive 1.5%.…”
Section: Discussionsupporting
confidence: 81%
“…15,16 In a study conducted by Nolte et al reported that in seventeen male patients, those who underwent (transjugular intrahepatic port systemic stent shunting), 30% -70% erectile dysfunction increased. 17 In another study by James H et al also showed partial sexual dysfunction in the 20.6% and complete dysfunction in the 34.3% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have systematically investigated SD in women with CHC. Soykan et al performed a cross-sectional study of 46 IFN-α-naive CHC patients and found higher rates of SD in women (50%) than in men (21%) 14 . More recently, Elshimi et al evaluated SD in women with CHC before IFN-α treatment and in controls 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our symptom measure did not ask about sexual symptoms related to HIV or HCV infection, and no participant discussed sexual symptoms in response to open-ended interview questions. However, recent data and clinical experience indicate that sexual functioning and symptoms (e.g., impotence) may be related to HCV infection (Ferri, Bertozzi, & Zignego, 2002;Soykan et al, 2005). Future studies will need to include specific measures of sexual symptoms in studies of adults with HIV/HCV co-infection.…”
Section: Limitationsmentioning
confidence: 99%